2016
DOI: 10.1088/1475-7516/2016/08/026
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hubble constant: non-Gaussian errors in HST Key Project data

Abstract: Abstract. Assuming the Central Limit Theorem, experimental uncertainties in any data set are expected to follow the Gaussian distribution with zero mean. We propose an elegant method based on Kolmogorov-Smirnov statistic to test the above; and apply it on the measurement of Hubble constant which determines the expansion rate of the Universe. The measurements were made using Hubble Space Telescope. Our analysis shows that the uncertainties in the above measurement are non-Gaussian.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For example, the observed data may not be a random sample of independent, identically distributed variables (need to test the critical linear combinations of variables), or the observed distribution of data may be heavy-tailed. Apparently, there is no guarantee that the Gaussian feature is invariant for the astronomical data (Chen et al 2003;Crandall et al 2015;Singh et al 2016;Zhang 2017). Similarly, for simple linear regression, one of model assumptions explicitly indicate that the probability distribution of the random component is normal (Mendenhall & JSincich 2011).…”
Section: Analysis Of Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the observed data may not be a random sample of independent, identically distributed variables (need to test the critical linear combinations of variables), or the observed distribution of data may be heavy-tailed. Apparently, there is no guarantee that the Gaussian feature is invariant for the astronomical data (Chen et al 2003;Crandall et al 2015;Singh et al 2016;Zhang 2017). Similarly, for simple linear regression, one of model assumptions explicitly indicate that the probability distribution of the random component is normal (Mendenhall & JSincich 2011).…”
Section: Analysis Of Methodologymentioning
confidence: 99%
“…In observed astrophysical fields, Gaussian statistics has been an important point followed by astronomers with great interests for quite a long time. However, Chen et al (2003), Singh et al (2016) and Bailey (2017) have demonstrated that the prior assumptions can not arbitrarily depend on the normality. Clearly, other more robust approaches are needed.…”
Section: Confidence Intervals and Bootstrap Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another non-negligible point is the heavytailed problem of the observed distribution. Essentially, no one can be accurately aware whether or not the normality feature is intrinsic for the measurement data [12,16,55,57,58].…”
Section: Discussionmentioning
confidence: 99%